The effect of intravitreal administration of bevacizumab on macular edema and visual acuity in age-related macular degeneration with subfoveolar choroidal neovascularisation - Ristić Dragana; Vukosavljević Miroslav; Draganić Biljana; Cerović Vesna; Petrović Nenad; Janićijević-Petrović Mirjana (Vojnosanitetski Pregled)
Background/Aim. Age-related macular degeneration (AMD) is a leading cause of the loss of central visual acuity in population older than 70 years. We can distinguish wet and dry form of AMD. The aim of the study was to present our early results in treatment of the wet (neovascular) form of AMD with intravitreal administration of bevacizumab. Methods. The study included 39 patients. Each patient underwent a complete ophthalmological examination, fluorescein angiography (FA) and optical coherence tomography (OCT). All the patients received 1.25 mg of intravitreal bevacizumab (0.05 mL of commercial phial of Avastin®). The total of three doses was given with a one-month interval between doses. Results. Among 39 patients, 24 were women and 15 men. The average best corrected visual acuity (BCVA) was improved from 0.09 before the therapy to 0.24 after the administration of all the three doses of bevacizumab (p < 0.001). The average central macular thickness (CMT) measured by OCT was improved from 474 μm in the beginning to 341 μm after the administration of all the three doses of the drug (p < 0.001). There were no side effects. Conclusions. Our short-term experience indicates that intravitreal administration of three doses of bevacizumab in one-month intervals between the doses leads to a significant reduction of macular edema and improvement of BCVA in patients with neovascular AMD.